Evaluating automated emergency braking performance in simulated car-to-two-wheeler crashes in China: A comparison between C-NCAP tests and in-depth crash data. (September 2021) - Sui, Bo; Lubbe, Nils; Bärgman, Jonas
Highlights: With 70° AEB sensor FoV, all crashes in the current C-NCAP test dataset were avoided. With 70° AEB sensor FoV, less than 50% of SHUFO car-to-TW crashes were avoided. Turning scenarios are difficult to avoid and should be added to the current C-NCAP. Higher TW speeds in perpendicular crashes should also be added to the current C-NCAP. Many high impact speed (>40 km/h) crashes likely to remain after TW-AEB is ubiquitous. Abstract: Automated Emergency Braking (AEB) is an effective way to prevent crashes from happening or mitigate their severity. Because riders of two-wheelers (TWs) are among the most vulnerable road users, New Car Assessment Programs, like the China New Car Assessment Program (C-NCAP), have recently introduced test scenarios for the assessment of AEB for cars encountering TWs (TW-AEB). The main aim of this study was to determine how well two different C-NCAP test scenario datasets reflect real-world crash scenarios for the purpose of assessing TW-AEB performance. We used virtual counterfactual simulations to determine whether the hypothetical TW-AEB's performance, when applied to the two C-NCAP datasets, was similar to its performance when applied to a set of reconstructed car-to-TW crashes representing real-world crashes. The test datasets were the current C-NCAP scenario set and a proposed C-NCAP scenario set; the real-world crash dataset comprised 113 reconstructed crashes from the Shanghai United Road Traffic Safety Scientific Research Center database (SHUFO). The performances were compared with respect to crash avoidance rate and the characteristics of the remaining crashes. A substantially higher proportion of crashes was avoided in the current C-NCAP scenario set than in the other two (with the sensor field of view (FoV) set to 70° and the activation time to 1.1 s TTC). In fact, with these parameter settings, no crashes remained in the current C-NCAP scenarios, while only 37% and 46% of the crashes in the proposed C-NCAP scenario set and SHUFO crash set were avoided, respectively. Our findings show that TW-AEB systems which are optimized for the current C-NCAP test scenarios are likely to provide benefits in real-world crashes. However, including additional test scenarios which reflect real-world crash situations more accurately would likely lead to a higher correlation between C-NCAP scores and real-world TW-AEB performance. In particular, we recommend the introduction of longitudinal same-direction scenarios with the car or TW turning and perpendicular scenarios with high TW traveling speed, in future C-NCAP releases. Inclusion of these scenarios in C-NCAP might reward improvements of future TW-AEBs toward systems that can save more lives. Furthermore, our study shows that there is likely to be a substantial number of crashes with an impact speed higher than 40 km/h still remaining even after the widespread application of TW-AEB. Therefore, passive safety for TW riders on Chinese roads will be still needed.